elexiko: A Corpus-Based Monolingual German Dictionary - Storjohann, Petra (HERMES - Journal of Language and Communication in Business, 2005)
This article provides an introduction to elexiko, the ﬁrst German hypertext dictionary to be compiled on a corpus basis, which is currently being developed at the Institut für Deutsche Sprache Mannheim (IDS). First, a brief account of the design is given, followed by a demonstration of the methods and tools that are being employed to compile it. elexiko will provide not only an improved quantity of lexical information, but also a new quality of information which will be explained and illustrated at different levels of the microstructure of the dictionary. The description of word meaning and use in elexiko will be presented in detail, with a particular focus on the treatment of collocations, ambiguity, vagueness, and the presentation of senses. The development of a theoretically grounded procedure for lexicographic disambiguation is also described. This is then followed by a brief account of the treatment of grammatical details. Finally, issues of usability, the progress of the project and its future perspectives will be considered.